HIV Drug Resistance Mutations in Patients with HIV and HIV-TB Coinfection After Failure of First-Line Therapy: A Prevalence Study in a Resource-Limited Setting. (22nd May 2019) - Khan, Nawaid Hussain; Kohli, Mikashmi; Gupta, Kartik; Das, Bimal Kumar; Pandey, Ravindra Mohan; Sinha, Sanjeev
Introduction: The present study aimed to report the prevalent HIV-1 drug-resistant mutations in patients with HIV-1 alone and tuberculosis (TB) coinfection alone to improve our understanding of the mutation patterns and aid treatment decisions. Methods: Patients with HIV-1 and HIV-TB on treatment for more than 1 year with suspected failure were recruited. Sequencing of protease and two-thirds of the region of reverse transcriptase gene was done for drug-resistant mutations. Results: In the HIV-TB group (n = 25), 88%, 92%, and 12% had mutations to nucleoside reverse transcriptase inhibitors (NRTIs), non-nucleoside reverse transcriptase inhibitors (NNRTIs), and protease inhibitors (PIs), respectively. In the HIV-alone group (n = 25), 84%, 100%, and 4% had mutations to NRTIs, NNRTIs, and PIs, respectively. M184V, M41L, D67N, G190A, A98G, and K103N were the most common mutations seen. Conclusion: There is a high prevalence of drug-resistant mutations in HIV and HIV-TB coinfected patients.